Relationship of Related Party Transactions and Earnings Management - Nur Astri Sari; Rusma Nailiah; Achmad Suhaili; Fitria Handayani (AFEBI Accounting Review, 2020)
This study aimed to examine the relationship between related party transactions and earnings management. The sample of this study was companies listed on the Indonesia Stock Exchange for the 2017 and 2018 period. The result shows that related party transaction (sales and expense) has a negative effect on accrual earnings management. It indicates that firms use related party transactions (sales and expense) as substitutes for earnings management especially accrual earnings management.